Levels of select PCB and PBDE congeners in human postmortem brain reveal possible environmental involvement in 15q11‐q13 duplication autism spectrum disorder - Michelle M. Mitchell; Rima Woods; Lai‐Har Chi; Rebecca J. Schmidt; Isaac N. Pessah; Paul J. Kostyniak; Janine M. LaSalle (2012)
Abstract Persistent organic pollutants (POPs), including polychlorinated biphenyls (PCBs) and polybrominated diphenylethers (PBDEs) that bioaccumulate in lipid‐rich tissues are of concern as developmental neurotoxicants. Epigenetic mechanisms such as DNA methylation act at the interface of genetic and environmental factors implicated in autism‐spectrum disorders. The relationship between POP levels and DNA methylation patterns in individuals with and without neurodevelopmental disorders has not been previously investigated. In this study, a total of 107 human frozen postmortem brain samples were analyzed for eight PCBs and seven PBDEs by GC‐micro electron capture detector and GC/MS using negative chemical ionization. Human brain samples were grouped as neurotypical controls ( n = 43), neurodevelopmental disorders with known genetic basis ( n = 32, including Down, Rett, Prader‐Willi, Angelman, and 15q11‐q13 duplication syndromes), and autism of unknown etiology ( n = 32). Unexpectedly, PCB 95 was significantly higher in the genetic neurodevelopmental group, but not idiopathic autism, as compared to neurotypical controls. Interestingly, samples with detectable PCB 95 levels were almost exclusively those with maternal 15q11‐q13 duplication (Dup15q) or deletion in Prader‐Willi syndrome. When sorted by birth year, Dup15q samples represented five out of six of genetic neurodevelopmental samples born after the 1976 PCB ban exhibiting detectable PCB 95 levels. Dup15q was the strongest predictor of PCB 95 exposure over age, gender, or year of birth. Dup15q brain showed lower levels of repetitive DNA methylation measured by LINE‐1 pyrosequencing, but methylation levels were confounded by year of birth. These results demonstrate a novel paradigm by which specific POPs may predispose to genetic copy number variation of 15q11‐q13. Environ. Mol. Mutagen., 2012. © 2012 Wiley Periodicals, Inc.